2015
DOI: 10.1002/jsfa.7142
|View full text |Cite
|
Sign up to set email alerts
|

Silicon biofortification of leafy vegetables and its bioaccessibility in the edible parts

Abstract: The application of Si to the nutrient solution in the range of 50-100 mg L(-1) allows biofortification of leafy vegetables. In addition, the biofortified vegetables showed, on average, more bioaccessible Si, with respect to unbiofortified vegetables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 39 publications
(61 reference statements)
7
37
0
1
Order By: Relevance
“…At the same time, Swiss chard showed slightly lower bioaccessibility of oxalate. According to previous studies [2][3][4][5] the bioaccessibility of mineral nutrients can be considerably affected by several factors, including mineral type and food matrix composition. At any rate, all the results of the present study suggest that bioaccessibility, defined as the ability of a nutrient to be released into the gastrointestinal tract, can be considered as a useful tool to better estimate real nutrient intake from vegetable products, especially when innovative cultivation protocols are applied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, Swiss chard showed slightly lower bioaccessibility of oxalate. According to previous studies [2][3][4][5] the bioaccessibility of mineral nutrients can be considerably affected by several factors, including mineral type and food matrix composition. At any rate, all the results of the present study suggest that bioaccessibility, defined as the ability of a nutrient to be released into the gastrointestinal tract, can be considered as a useful tool to better estimate real nutrient intake from vegetable products, especially when innovative cultivation protocols are applied.…”
Section: Discussionmentioning
confidence: 99%
“…A novel challenge in agriculture is the production of tailored foods, i.e., foods specifically suitable for target groups of people with particular nutritional needs. In fact, in recent years, a number of studies have highlighted the possibility of producing vegetables for specific physiological conditions, such as biofortified vegetables, with the aim of counteracting different nutritional deficits [1][2][3][4][5][6][7][8]. In general, these authors reported evidence on the use of specific growing protocols aimed to increase the content of specific nutrients in plant tissues, such as iodine (I), silicon (Si), calcium (Ca), selenium (Se), zinc (Zn), and iron (Fe).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon (Si) is a general mineral component present in many food plants, including cereals, fruit, vegetables and legumes 5 . The Si content in plant tissues is generally related with species 6 7 . Its absorption in the intestinal tract is related to the food source.…”
mentioning
confidence: 99%
“…Silicon helps plants tolerate different environmental stresses that are present in field conditions, such as high temperature, drought, loading, UV, freezing, nutrient imbalance, salinity, and metal toxicity (Sahebi et al 2015). A number of studies have shown that Si treatment improves crop growth and yield under abiotic and biotic stress conditions (Ahmad et al 2013a, b;Esfahani et al 2014;Schurt et al 2014;Artyszak et al 2015;Chen et al 2015;D'Imperio et al 2015;Hartley 2015;Hussain et al 2015;Muneer and Jeong 2015;Noor et al 2015;Saudy and Mubarak 2015;Wang et al 2015;Xu et al 2015;Yin et al 2015).…”
Section: Introductionmentioning
confidence: 96%